Shell-dependent photofragmentation dynamics of a heavy-atom-containing bifunctional nitroimidazole radiosensitizer - Pihlava, Lassi (Royal Society of Chemistry, 2026)
Radiation therapy uses ionizing radiation to break chemical bonds in cancer cells, thereby causing DNA damage and leading to cell death. The therapeutic effectiveness can be further increased by making the tumor cells more sensitive to radiation. Here, we investigate the role of the initial halogen atom core hole on the photofragmentation dynamics of 2-bromo-5-iodo-4-nitroimidazole, a potential bifunctional radiosensitizer. Bromine and iodine atoms were included in the molecule to increase the photoionization cross-section of the radiosensitizer at higher photon energies. The fragmentation dynamics of the molecule was studied experimentally in the gas phase using photoelectron–photoion–photoion coincidence spectroscopy and computationally using Born–Oppenheimer molecular dynamics. We observed significant changes between shallow core (I 4d, Br 3d) and deep core (I 3d) ionization in fragment formation and their kinetic energies. Despite the fact, that the ions ejected after deep core ionization have higher kinetic energies, we show that in a cellular environment, the ion spread is not much larger, keeping the damage well-localized.